Madurez en la gestión de proyectos. Un análisis de tendencias. - Hugo Fernando Castro-Silva; Torcoroma Velásquez-Pérez; Johan Sebastián Méndez-López (Mundo Fesc)
Maturity models are tools that guide organizations on their journey from process standardization and the consolidation of a project management culture to project management excellence, with the goal of achieving a competitive advantage. This research aims to identify the evolution and trends in research related to project management maturity. A validated systematic literature review methodology was used. The results demonstrate that the origins of the study of this field of knowledge date back to the early decades of the 20th century in the field of quality assurance and process improvement. Current models incorporate elements of sustainability and Industry 4.0 into their maturity models. The most frequently cited maturity models in the scientific literature are also identified, along with their convergent and divergent elements